2021
DOI: 10.1038/s41598-020-79648-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide methylation profiling of selected matched soft tissue sarcomas identifies methylation changes in metastatic and recurrent disease

Abstract: In this study we used the Illumina Infinium Methylation array to investigate in a cohort of matched archival human tissue samples (n = 32) from 14 individuals with soft tissue sarcomas if genome-wide methylation changes occur during metastatic and recurrent (Met/Rec) disease. A range of sarcoma types were selected for this study: leiomyosarcoma (LMS), myxofibrosarcoma (MFS), rhabdomyosarcoma (RMS) and synovial sarcoma (SS). We identified differential methylation in all Met/Rec matched samples, demonstrating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…The reduced level of Ventx in CLL cells promoted Wnt/β-cat and LEF/TCFs interaction, and in turn, induced cyclin D1 expression, leading to cell proliferation and cancer progression. Recently, it was reported that the differential methylation level of Ventx was significantly implicated in sarcoma progression in humans [ 114 ]. A genome-wide methylation-profiling study in metastatic and recurrent sarcomas showed that Ventx was hypermethylated in metastasis pleomorphic rhabdomyosarcoma (Ple-RMS, a rare, aggressive sarcoma with poor prognosis), as compared to primary Ple-RMS.…”
Section: Human Ventx (Vent-like Homeobox Protein 2)mentioning
confidence: 99%
“…The reduced level of Ventx in CLL cells promoted Wnt/β-cat and LEF/TCFs interaction, and in turn, induced cyclin D1 expression, leading to cell proliferation and cancer progression. Recently, it was reported that the differential methylation level of Ventx was significantly implicated in sarcoma progression in humans [ 114 ]. A genome-wide methylation-profiling study in metastatic and recurrent sarcomas showed that Ventx was hypermethylated in metastasis pleomorphic rhabdomyosarcoma (Ple-RMS, a rare, aggressive sarcoma with poor prognosis), as compared to primary Ple-RMS.…”
Section: Human Ventx (Vent-like Homeobox Protein 2)mentioning
confidence: 99%
“…Deregulation of this epigenetic mechanism has major implications for cancer development and progression ( Diaz-Lagares et al, 2016 ). In this context, recent genome-wide analyses have revealed striking alterations in the methylation profile of uterine uADC and uLMS ( Zhang et al, 2014 ; Kommoss et al, 2020 ; Vargas et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, low level of CNV (copy gain/loss) in MFS was reported as well as methylation alterations in several genes ( MEST , C14MC , FAM136A , SNRPG , CCND2 , TBX15 , PLEC1 , CDH15 ), data which are in accordance with Ogura’s study. 22 , 40 Importance of methylation studies has been mentioned also in the only study available to date using WES and SNP arrays to investigate 20 sarcomas including five MFS, which showed a gradual increase of both nucleotide- and chromosome-level mutations. In particular, they reported that MFS has complex copy number changes but few significant single nucleotide variants.…”
Section: Diagnosis and Prognosismentioning
confidence: 99%